The Role of Internal Audit in Preventing Irregularities and Fraud in Terms of Computer Data Processing - Mahaček, Dubravla; Bolfek, Berislav; Šakota, Bernarda (Oeconomica Jadertina, 2017)
Illegalities and irregularities in the business conduct of enterprises are increasingly common phenomenon, which affects the data reported in financial statements. Therefore, in addition to carrying out the external audit it is necessary to establish internal control over financial reporting. Internal control over financial reporting consists of the policies and procedures of the company, and is designed and operates in order to provide reasonable assurance regarding the reliability of financial reporting and fair presentation of financial statements. Established internal control and internal audit also provide greater opportunities for detecting and preventing fraud and irregularities. Unwanted behaviour was favoured and accelerated by the development of computer technology. While on the one hand computer technology improves business results, on the other hand it facilitates the unauthorized practices and increases the possibility of financial fraud, as evidenced by the increasing number of computer fraud in various companies. Therefore, more attention should be given to new tools, techniques and auditing models to improve the quality and credibility of reporting. In an environment which is constantly changing, companies are exposed to a number of risks. Risk assessment and risk management have become an integral part of business activity at every organizational level. The aim of this paper is to determine whether the internal audit as an instrument of risk management can contribute in preventing irregularities and fraud in terms of computer data processing
Keywords: internal audit; responsibility internal audit; risk management; financial frauds; computer data processing